Taxol and β-tubulins from endophytic fungi isolated from the Himalayan Yew, Taxus wallichiana Zucc. - Vélëz, Heriberto; Gauchan, Dhurva Prasad; García-Gil, María del Rosario (Frontiers in Microbiology, 2022)
Paclitaxel, better known as the anticancer drug Taxol®, has been isolated from several plant species and has been shown to be produced by fungi, actinomycetes, and even bacteria isolated from marine macroalgae. Given its cytostatic effect, studies conducted in the 1990s showed that paclitaxel was toxic to many pathogenic fungi and oomycetes. Further studies led to the idea that the differences in paclitaxel-sensitivity exhibited by different fungi was due to differences in the β-tubulin protein sequence. With the recent isolation of endophytic fungi from the leaves and bark of the Himalayan Yew, Taxus wallichiana Zucc., and the availability of genomes from paclitaxel-producing fungi, we decided to further explore the idea that endophytic fungi isolated from Yews should be well-adapted to their environment by encoding β-tubulin proteins that are insensitive to paclitaxel. Our results found evidence of episodic positive/diversifying selection at 10 sites (default p-value threshold of 0.1) in the β-tubulin sequences, corresponding to codon positions 33, 55, 172, 218, 279, 335, 359, 362, 379, and 406. Four of these positions (i.e., 172, 279, 359, and 362) have been implicated in the binding of paclitaxel by β-tubulin or formed part of the binding pocket. As expected, all the fungal endophytes grew in different media regardless of the paclitaxel concentration tested. Furthermore, our results also showed that Taxomyces andreanae CBS 279.92, the first fungus shown to produce paclitaxel, is a Basidiomycete fungus as the two beta tubulins encoded by the fungus cluster together with other Basidiomycete fungi.